Use of on-line marketing in the Czech real estate market - Ilinskaya, Ekaterina; Cook, Gina, 1970-; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The goal of this Master's Thesis is to evaluate the use of online marketing tools used by the Prague-based Real Estate company Happy House Rentals Ltd. and to propose improvements for their online marketing strategy. The first part of the paper describes available online marketing tools. The second part introduces the Real Estate market and describes, using published data, the situation of the Real Estate industry in the Czech Republic and Prague metropole in particular. This is followed by a primary analysis of the web presence of Prague's Real Estate Agencies fitting the competitive profile of Happy House Rentals Ltd. The third part is a case study on the online marketing presence of Happy House Rentals Ltd. Using the tools and data introduced in the first two parts of this Master's Thesis, the author suggests improvements for the online marketing strategy of Happy House Rentals Ltd.
Vedoucí práce: Gina Cook
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses